Local Government Efforts in Control of Inflation in Papua's Highlands Province - Syamsul Bahri Abd. Rasyid; Ilham Ilham; Misran Misran (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2025)
This research describes the efforts of the Papua’s Highlands Province government in controlling inflation, including policy implications and recommendations that may serve as a reference for future governance. A Qualitative research method was employed using the Miles–Huberman analysis model, supported by NVivo 12 Plus for qualitative coding and VOSviewer for bibliometric analysis. The findings show that inflation is a priority program for the provincial government. Efforts undertaken include restructuring the Regional Inflation Control Team (TPID), establishing a small secretariat team, strengthening the logistics system, improving the Trans Papua Road segment through a Public–Private Partnership (PPP) scheme—particularly the severely damaged Wamena–Jayapura corridor—and promoting local food sovereignty. Special autonomy authority, flexible policy instruments, and adequate development funding are expected to lay a strong foundation for long-term stability and economic sustainability in Papua’s Highlands Province, including maintaining a stable inflation rate.